Mechanical behaviour of concrete made with fine recycled concrete aggregates - Evangelista, Luís (2020)
This paper concerns the use of fine recycled concrete aggregates to partially or globally replace natural fine aggregates (sand) in the production of structural concrete. To evaluate the viability of this process, an experimental campaign was implemented in order to monitor the mechanical behaviour of such concrete. The results of the following tests are reported: compressive strength, split tensile strength, modulus of elasticity and abrasion resistance. From these results, it is reasonable to assume that the use of fine recycled concrete aggregates does not jeopardize the mechanical properties of concrete, for replacement ratios up to 30%.